Programa para la prevención de conducta antisocial en los adolescentes - Ortega Sagbay, Jenny Soraya (My University, 2021)
The adolescence is a stage that experiences changes and experiences, a period where the psychosocial factors of the context lead to the risk of adopting antisocial behavior, a term that is characterized in maladaptive behaviors such as restricting norms and laws established by society, performing acts that go in Against the integrity of oneself and of another person, possessing emotional uncontrols such as anger and aggressive impulses, those particularities cause psychological, behavioral and criminal consequences incited by the lack of social ability that affects the interpersonal and social area of the subject. For this reason, a primary prevention program for antisocial behavior in adolescents was designed, which has a structure of ten sessions according to the proposed objective, time varied from sixty to ninety minutes with an approximate duration of two months and fifteen days more, until the established sessions are completed. The program has the objective of preventing antisocial behavior through psychological techniques to potentiate adaptive behaviors. For its design, bibliographic reviews of scientific articles and books appropriate to research were carried out, which allowed the gathering of necessary, adequate and truthful information. For the creation of the program, psychological techniques were implemented according to the needs of the beneficiaries and creative dynamics adaptable to age, the activities carried out are aimed at psychoeducation of important elements related to the program and reinforcing social skills aimed at self-control, assertiveness and self-control. ability to solve problems in order to provide adaptive behaviors.
La adolescencia es una etapa que experimenta cambios y experiencias, período donde los factores psicosociales del contexto conducen al riesgo de adoptar una conducta antisocial, término que se caracteriza en comportamientos desadaptativos como el restringir normas y leyes establecidos por la sociedad, realizar actos que vayan en contra de la integridad de sí mismo y de otra persona, el poseer descontroles emocionales como la ira e impulsos agresivos, aquellas particularidades provocan consecuencias psicológicas, conductuales y penales incitadas por la carencia de habilidad social que repercute en el área interpersonal y social del sujeto. Por la presente razón, se diseñó un programa de prevención primaria para la conducta antisocial en los adolescentes, que dispone de una estructura de diez sesiones acorde al objetivo planteado, tiempo variado de sesenta a noventa minutos con una duración aproximada de dos meses y quince días más, hasta que se completen las sesiones establecidas. El programa tiene el objetivo de prevenir la conducta antisocial mediante técnicas psicológicas para potencializar comportamientos adaptables, para el diseño del mismo, se realizó revisiones bibliográficas de artículos científicos y libros apropiados a la investigación que permitieron recabar información necesaria, adecuada y verídica. Para la creación del programa se implementó técnicas psicológicas acorde a las necesidades de los beneficiarios y dinámicas creativas adaptables a la edad, las actividades que se ejecutan son dirigidos a psicoeducar elementos importantes relacionados al programa y reforzar las habilidades sociales dirigidas al autocontrol, asertividad y la capacidad de resolver problemas con la finalidad de proveer conductas adaptables.
Keywords: CONDUCTA ANTISOCIAL; ADOLESCENTE; PROGRAMA; PREVENCION